Perovskite Solar Cells: Cesium Doped NiOx as an Efficient Hole Extraction Layer for Inverted Planar Perovskite Solar Cells (Adv. Energy Mater. 19/2017) - Chen, Wei; Liu, Fang‐Zhou; Feng, Xi‐Yuan; Djurišić, Aleksandra B.; Chan, Wai Kin; He, Zhu‐Bing (Advanced energy materials, 2017)
In article number 1700722, Aleksandra B. Djurišić, Zhu‐Bing He, and co‐workers investigate the cesium doped NiO film as highly transparent and conductive HTL for inverted perovskite solar cells. Cs dopant can significantly improve the conductivity of NiO and lower the work function, allowing better charge transfer and band alignment between perovskite and Cs doped NiO. Efficiency over 19% for the Cs doped devices is obtained and 90% of its initial performance is maintained after 80 days.